USE OF MODERN MARKETING CONCEPTS IN THE ACTIVITIES OF ENTERPRISES IN THE CONDITIONS OF INNOVATIVE AND DIGITAL ECONOMY - Mamatkulova Shoira Jalolovna (Web of Journals Publishing, 2023)
The article describes ways to use modern marketing concepts in the activities of enterprises in the conditions of innovation and the digital economy.
Keywords: innovation, digital economy, competition, marketing, concept, strategy.